Depression Following Athletic Retirement in Elite Athletes: A Review of Risk Factors, Neurobiological Mechanisms, and Preventive Strategies - Iwanowska, Martyna; Flis, Beata; Cyrzan , Alicja; Zalewski, Jakub Z.; Zysk, Adam; Ząbek, Mateusz; Fronczak, Bartosz; Goss, Adrian; Styczyńska, Małgorzata; Wojewódzki, Maciej (Journal of Education, Health and Sport, 2026)
Background. Depression is one of the most common mental disorders worldwide and a significant public health concern. In elite athletes, particular attention has been given to the transition period following career termination, which involves numerous biological, psychological, and social changes that may increase the risk of mood disorders. Aim. This review aims to present current knowledge on the epidemiology, risk factors, and neurobiological mechanisms of depression following athletic retirement, and to discuss preventive strategies and future research directions. Material and Methods. This is a narrative review based on an analysis of the available scientific literature on the mental health of elite athletes, with particular emphasis on the post-career period. Results. Available data indicate that depressive symptoms occur in approximately 15-30% of former athletes, particularly within the first years after career termination. Major risk factors include strong athletic identity, involuntary retirement, lack of alternative career pathways, chronic pain, and repetitive head injuries. Neurobiological mechanisms also play a significant role, including dysregulation of the HPA axis, neuroinflammatory processes, and alterations in neurotransmitter systems. Conclusions. Depression following sports career termination is a complex biopsychosocial issue. Effective prevention requires early, systemic, and interdisciplinary approaches that encompass both the active career period and the transition to post-sport life. Further research, particularly prospective studies, is necessary to better understand the underlying mechanisms and to develop effective support strategies.